The Phenomenon of Online Lending Ads on Tiktok Social Media among West Java Students - Alindra Rahma Dewi; Asri Nurpalah; Farida Nurfalah; Welly Wihayati (Greenation International Journal of Economics and Accounting, 2025)
Online lending is currently on the rise in Indonesia. This trend is driven by the growing economic sector and the rapid advancement of digital technology. Online lending services are increasingly advertised on social media platforms, including TikTok, which is widely used by university students. This study aims to explore the phenomenon of online loan advertisements on TikTok among university students in West Java. The subjects were selected using purposive sampling, resulting in five informants who were interviewed. The data collected in this study were analyzed using thematic analysis. Through in-depth interviews with the informants, it was found that dynamic visuals, popular music, and persuasive narratives are the main strategies employed by advertisers to capture attention and generate interest among students. This interest is further reinforced by offers that appear to provide instant solutions to financial needs, thereby triggering a desire to try the service. However, at the action stage, not all informants immediately used online loan services. Most students still considered the associated risks, including high interest rates, the potential for fraud, and social pressure from their surroundings.